Twitter data analysis of ministries, department and agencies in Nigeria (2019)
The use of social media tools as a means of communication by various ministries, departments and agencies (MDAs) in Nigeria started very late compared with personal use or in the private or corporate sector. The social media tool of interest is Twitter which is a microblogging application and it is becoming a momentous element of the public sector social media agenda. The study revealed the interest of citizens in the activities of the various MDAs in the country, some MDAs are not known to be too active since their activities are not given the required coverage in the contemporary media or the sector seems not to be receiving adequate attention and patronage. This paper made an empirical and methodological contribution to this new body of knowledge by presenting an overview study of general Twitter accounts maintained by the various MDAs of the Nigerian government. Over 70,000 tweets were used from 64 officially available Twitter accounts. It was discovered that the gradual use of Twitter is really creating a more engaging opportunity for the citizens to have firsthand information about the activities of the government agencies. The study revealed that the trend progressed over the years, that is, there was an upward movement in the use of twitter as a means of government citizen engagement over a 10 years’ period. It was discovered that the use of twitter was very high during the office hours and more activities between Mondays and Fridays. The Nigerian Football Federation led the first five MDAs. Most of the devices used by MDAs to access are laptops or desktops, followed by smart phones. Android devices are more in use than iPhone devices. The remaining devices are not popular in the public services.